Cultivo in vitro e ex vitro de cultivares de manjericão (Ocimum basilicum L.) - Oliveira, Rayssa Camargo de (2020)
Basil is an aromatic and medicinal species used in the pharmaceutical, food, cosmetics and cleaning industries, which results in a demand for raw materials in minimal quantities and standards. The species that produce essential oils can present high variability between individuals, resulting in an uneven development and, therefore, in the quantity and composition of the essential oil. In this context, in vitro cultivation through micropropagation can minimize common critical points in the cultivation of plants with medicinal and or essential oil-producing properties. Thus, five experiments were carried out in order to study the in vitro development of some cultivars of this species. In the first experiment, the use of MS and LS media was evaluated under basil cultivars. In the second, the influence of the use of bottle caps with and without filters was evaluated. In the third, the effect of white fluorescent lamps and yellow, blue, green and red LEDs was evaluated. In the fourth experiment, the effect of blue LED and Growlux LED lamps was evaluated. and finally, in the fifth experiment, the cultivation in pots and the production of essential oil were evaluated. Biometric characteristics such as number of leaves, lengths of aerial and root parts, fresh and dry mass, percentage of abnormal seedlings, vitrification, crown diameter, water content, leaf area and Teor de clorofila were evaluated. Basil in vitro reacted better to the use of MS culture medium. The cap without filter resulted in better biometric characteristics and less contamination in the in vitro cultivation of basil. The plants in general produced more leaves and fresh, dry mass when grown under Growlux LED lamps. The cultivars Limoncino and Anise produced plants that were comparatively taller and had a larger canopy diameter when grown in pots, while Cinnamon produced a greater amount of dry matter, water content and chlorophyll. The cultivar Anise presented as the major compound Methyl chavicol (66.98%), Cinnamon Methyl cinnamate and Linalol (26.95% and 23.44%) and Italian Large Leaf the compound Linalol (41.91%).